2021
DOI: 10.3389/fcell.2021.732036
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in Gastric Cancer: From Malignant Hallmarks to Clinical Applications

Abstract: Gastric cancer (GC) is one of the most lethal malignancies worldwide. However, the molecular mechanisms underlying gastric carcinogenesis remain largely unknown. Over the past decades, advances in RNA-sequencing techniques have greatly facilitated the identification of various non-coding RNAs (ncRNAs) in cancer cells, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). Accumulating evidence has revealed that ncRNAs are essential regulators in GC occurrence and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 177 publications
(211 reference statements)
0
11
0
Order By: Relevance
“…Based on the association observed between lncRNA and GC progression, it is possible to assume that specific lncRNAs will shortly be used as clinical biomarkers for the diagnosis and prognosis of GC patients. In addition, lncRNAs are also recognized as therapeutic targets or therapeutic agents for GC patients (21). Compared with proteincoding genes, lncRNA therapy exhibits several advantages: Firstly, lncRNAs are highly abundantly expressed in humans with about 5,400 to more than 10,000 lncRNA transcripts (162), indicating that lncRNAs could be more accessible targets for cancer therapy.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the association observed between lncRNA and GC progression, it is possible to assume that specific lncRNAs will shortly be used as clinical biomarkers for the diagnosis and prognosis of GC patients. In addition, lncRNAs are also recognized as therapeutic targets or therapeutic agents for GC patients (21). Compared with proteincoding genes, lncRNA therapy exhibits several advantages: Firstly, lncRNAs are highly abundantly expressed in humans with about 5,400 to more than 10,000 lncRNA transcripts (162), indicating that lncRNAs could be more accessible targets for cancer therapy.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…In fact, the aberrant expression of lncRNAs has been observed in GC samples and cell lines (17,18). A growing amount of evidence suggests that lncRNAs are involved in practically all aspects of GC progression, including drug resistance (19)(20)(21). Exosomes are a novel extracellular vesicles that play crucial roles in cancer progression by transferring multiple biologically active molecules, such as proteins, lipids, and lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…The global incidence of stomach cancer estimated in 2020 was approximately 1089100 new cases and 768800 cancer deaths ( Figure 1 ). In recent years, a rising body of evidence has revealed that miRs are dysregulated in almost all types of tumors, including gastric, modulating the proliferation, stemness, tumor immune escape, invasion, angiogenesis, and drug resistance of tumor cells ( Chen et al, 2021 ). Some studies in which miRs play a major role in mediating DDP-resistance in stomach cancer will be detailed in Table 3 .…”
Section: The Top Five Deadliest Cancermentioning
confidence: 99%
“…In addition, accumulating studies identify non-coding RNAs including micro (mi)RNA, circular (circ)RNA and long-noncoding RNA as having prognostic value. Although studies highlight the value of biomarkers, some limitations cannot be ignored, such as conclusions based on a single research cohort, inadequate multi-center validation, single marker, and small sample sizes (9)(10)(11)(12). Therefore, new biomarkers with high accuracy and specificity are needed to improve the diagnosis and prognosis of GC.…”
Section: Introductionmentioning
confidence: 99%